IMPACCT Kids' Care: a real-world example of stakeholder involvement in comparative effectiveness research. (August 2015) - Likumahuwa-Ackman, Sonja; Angier, Heather; Sumic, Aleksandra; Harding, Rose L; Cottrell, Erika K; Cohen, Deborah J; Nelson, Christine A; Burdick, Timothy E; Wallace, Lorraine S; Gallia, Charles; DeVoe, Jennifer E
The Patient-Centered Outcomes Research Institute has accelerated conversations about the importance of actively engaging stakeholders in all aspects of comparative effectiveness research (CER). Other scientific disciplines have a history of stakeholder engagement, yet few empirical examples exist of how these stakeholders can inform and enrich CER. Here we present a case study which includes the methods used to engage stakeholders, what we learned from them, and how we incorporated their ideas in a CER project. We selected stakeholders from key groups, built relationships with them and collected their feedback through interviews, observation and ongoing meetings during the four research process phases: proposal development, adapting study methods, understanding the context and information technology tool design and refinement.